Electron Transfer and Multi‐Electron Accumulation in ExBox4+1. Issue 21 (19th May 2014) - Dyar, Scott M.; Barnes, Jonathan C.; Juríček, Michal; Stoddart, J. Fraser; Co, Dick T.; Young, Ryan M.; Wasielewski, Michael R.
Abstract Molecules capable of accepting and storing multiple electrons are crucial components of artificial photosynthetic systems designed to drive catalysts, such as those used to reduce protons to hydrogen. ExBox4+, a boxlike cyclophane comprising two π‐electron‐poor extended viologen units tethered at both ends by two p‐xylylene linkers, has been shown previously to accept an electron through space from a photoexcited guest. Herein is an investigation of an alternate, through‐bond intramolecular electron‐transfer pathway involving ExBox4+ using a combination of transient absorption and femtosecond stimulated Raman spectroscopy (FSRS). Upon photoexcitation of ExBox4+, an electron is transferred from one of the p‐xylylene linkers to one of the extended viologen units in ca. 240 ps and recombines in ca. 4 ns. A crystal structure of the doubly reduced species ExBox2+ was obtained.